Design and Development of Voltage, Current and Frequency Monitoring on 3-Phase Electrical Panel Boxes for Audio Sound Systems Using ESP32 Based Ubidots - Setiabudi, Arif; Harimurti, Rina; Suprianto, Bambang; Widayaka, Parama Diptya (Universitas PGRI Adi Buana Surabaya, 2024)
This research aims to design and build a monitoring system capable of measuring voltage, current, and frequency on 3-phase electrical panels for audio-sound systems. This system uses an ESP32 device as a microcontroller and Ubidots as a cloud platform for real-time data visualization and storage. Equipped with a PZEM004t as a voltage, current, and frequency sensor, this system provides accurate and real-time monitoring of electrical parameters. An analysis was carried out on the ability of this system to be accessed remotely via the network, as well as the integration of notifications via the Telegram application for direct notification of disturbances in the electrical panel. Testing was carried out by comparing this system with existing electrical panel boxes as well as through observation and assessment by five sound engineers to evaluate the system's performance in monitoring voltage, current, and frequency accurately and stably. The test results show that the system is capable of measuring and monitoring electrical parameters well, providing useful information for the maintenance and management of electrical systems, as shown by the results of the average map test error on the parameters voltage (0.4%), current (10% and frequency (0.6% and in usability testing, a percentage score of 97.5%. The implementation of this system is expected to increase the operational efficiency and reliability of the audio-sound system.